A noção corpo-olho e a fotografia documental de Marc Ferrez em exposição: um estudo cultural e comunicacional - Campos, Gabriela Alves (2021)
This work investigates exhibitions of the documentary photography of the 19th century and discusses the body-eye notion, by using cultural and communicational analysis (MONTEIRO; AZAMBUJA, 2018). This research involves a case study developed from field visits and the flanerie (BENJAMIN, 2006). The starting point for this research is the case study of the exhibition Marc Ferrez: Território e Imagem (2019 - 2020), by the Instituto Moreira Salles. From this exhibition, we discuss the photographic look (BOSI, 1988) and the visual messages contained in 19th century Brazilian documentar photography. By doing that, we perceive the mediation of visual productions as a possibility for the development of the way of look and of the activation of memory. The body-eye notion is developed through Crary's work (2014), aiming to address the complexity of the space of perception that resides between the way of look and the visual message. Therefore, this work reflects on the position of the observer (RACIÈRE, 2012) as an active and participant agent in the meaning space of the photographic exhibition and also reflects on the photographic exhibition as an active and participant agent in the meaning space of the observer. This dissertation comprises the plurality of analyzes and of possible investigations within the field of Image. Then, it opens the discussion of the body-eye notion as a proposal for multiple analysis of production, communication and consumption of photographic works.